(untitled) (TAJ: Journal of Teachers Association, 2018)
Fanconi Anemia (FA) is a rare autosomal recessive disorder associated with pancytopenia, spontaneous chromosomal instability and a variety of congenital anomalies. A variable phenotype and age of onset of anemia makes the diagnosis difficult in some cases. We report a case of Fanconi anemia who had triangular facies, hyperpigmentation, a few café-au-lait spots, microcephaly and short stature. Peripheral blood film showed pancytopenia, bone marrow study revealed aplasia and the patient had history of sibling (elder brother) death from same problem consistent with Fanconi anaemia. TAJ 2012; 25: 84-86